The Influence of Illustrated Folklore on Elementary School Students' Reading Interests - Mirda Indriani; Otang Kurniaman; Syahrilfuddin Syahrilfuddin (STAI Hubbulwathan Duri, 2023)
This study intends to evaluate the differences in the increase in reading interest of students who receive learning treatment using illustrated folklore books and students who study using books used in traditional learning. This research employed a quasi-experimental strategy using a matched-pairs control group. The 2022–2023 academic year's odd semester Indonesian language class was the setting for this study. Questions like